Artificial liver support systems for hepatitis B virus‐associated acute‐on‐chronic liver failure: A meta‐analysis of the clinical literature. Issue 2 (18th November 2022) - Li, Guotao; Zhang, Pan; Zhu, Yumeng
Abstract: To evaluate the short‐term and long‐term survival efficacy of an artificial liver support system (ALSS) in patients with acute‐on‐chronic liver failure (ACLF). A systematic search was performed for relevant published data in PubMed, Web of Science and Cochrane Library databases. Studies that evaluated the efficacy of ALSS in patients with ACLF and provided the short‐term or long‐term survival rate were included. A total of 10 studies involving 3685 patients were included in this analysis. The pooled 28‐day survival rate and 90‐day survival rate were 68.7% (95% CI: 64.5%–72.9%) and 53.4% (95% CI: 45.5%–61.4%), respectively. The pooled estimates of the OR for the 28‐day and 90‐day survival rates between the ALSS group and the control group were 1.91 (95% CI: 1.21–3.04) and 1.41 (95% CI: 1.17–1.70), respectively. Subgroup analysis showed that patients treated with lower levels of TBIL and MELD scores had a higher 28‐day survival rate ( χ 2 = 15.75, p < 0.01; χ 2 = 13.80, p < 0.01). The present meta‐analysis suggests that ALSS treatment could remarkably improve short‐term survival rates in HBV‐ACLF patients, which implies that treatment with ALSS may help to reduce high mortality. Further prospective randomized trials are needed to validate these findings.